We deserve monuments - Hammonds, Jas (Roaring Brook Press, 2022)
Seventeen-year-old biracial Avery Anderson's life is turned upside down when she and her parents move to Bardell, Georgia, to live with her terminally ill grandmother, Mama Letty. Avery's mom and Mama Letty have a strained relationship, but they won't tell Avery what caused it. Fortunately, Avery befriends Simone Cole, her Black next-door neighbor who she begins to fall for, and Jade Oliver, the White daughter of the town's most prominent family. As Avery begins to unpacks Bardell's racist past, she learns more about her own family's tragic connection to the town and about the unsolved murder of Jade's mother.